An Analysis of Limited Face-to-Face Learning at SMA Negeri 1 Bonehau - Riapratami, Gabriella; Firman, Firman; Amaliah, Nur (JURNAL BIOEDUKASI, 2025)
Limited face-to-face learning referred to classroom-based instruction conducted with certain restrictions. SMA Negeri 1 Bonehau was one of the schools that implemented limited face-to-face learning during the Covid-19 pandemic. The purpose of this study was to identify the implementation, teaching strategies used by educators, challenges encountered, and the impacts of limited face-to-face learning at SMA Negeri 1 Bonehau. A qualitative approach was employed in this research. The research subjects consisted of the vice principal for curriculum affairs, teachers, and students. Data were collected through in-depth interviews, observations, and documentation. The data were analyzed using the Miles and Huberman analysis model, which included data reduction, data display, and conclusion drawing. The findings showed that the implementation of limited face-to-face learning at SMA Negeri 1 Bonehau was in accordance with the official guidelines for classroom learning during the Covid-19 pandemic. Teachers prepared lesson summaries to be delivered to students. The challenges encountered included restricted instructional time, uneven internet access, limited availability of textbooks, difficulties in monitoring students’ compliance with physical distancing, and the large number of assignments students were required to complete.